KGB Activity against the Residents of Lithuania who Fled and Departed in the Sixth–Ninth Decade of the 20th Century - Juodis, Darius (Genocidas ir rezistencija, 2009)
The residents of Soviet Lithuania attempted in different ways to flee to the West. Most often they preferred escaping by sea (sailors) or separated from a tourist group when being abroad. Some made efforts to go to live in the West by obtaining permission from Soviet institutions.The Soviet penal codes attributed fleeing abroad to the grave crime against the state; the severest penalties were imposed for it. Until the beginning of the seventh decade, all refugees in their absence were sentenced to the death penalty by shooting. Later penalties were mitigated, in the same decade the practice of organizing the court processes in absentia was rejected. The criminal case just would be initiated and investigation would be conducted. The rehabilitation of the convicted and dismissal of the cases was started only at the end of the ninth decade.KGB persecuted the relatives and acquaintances of the persons who fled abroad, interrogated them, made searches in their homes, and controlled their correspondence.Soviet security planned and effected discrediting actions seeking to compromise refugees or departees abroad in the eyes of Lithuanian йmigrй or Lithuanian population. Disinformation was spread among the йmigrй about the supposed collaboration of those persons with KGB, reports were provided about their imaginary moral degradation. More serious results were not achieved in this field.KGB collected information on new refugees, who were disappointed with the life as emigrants. Taking advantage of their frustration moods, efforts were made to return them back to Lithuania. Within that period, just one refugee returned, but the role of Soviet security in this story is not quite clear.
Keywords: KGB; emigree; agents; repressions